Wednesday

April 16, 2014

April 16, 2014

Posted by **rinku** on Tuesday, April 9, 2013 at 1:31pm.

- algebra -
**Reiny**, Tuesday, April 9, 2013 at 2:43pmsimplified to

x^3 + 7x^2 - 21x - 27 = 0

try: x = ±1, ±3, ±7

on the second try, I got x=-1 to work

so (x+1) is a factor

by synthetic division I found

x^3 + 7x^2 - 21x - 27 = (x+1)(x^2 + 6x - 27) = 0

(x+1)(x+9)(x-3) = 0

x = -1, -9, and 3

**Related Questions**

MATH - solve 1-(2/x)=2/(x+2) Express your answer in simplest radical form. What ...

music urgent!!!!!!!!!!!! - i need help with annotating a piece of idian ...

algebra - Set the equations equal to each other so you can determine when the ...

Chemistry-help - I am rather confused about writing ionic equations. 1) SOLID ...

algerbra - 7(3x+4)=8(2x+5)+13 how would I start a equation like this would it be...

Calculus please help - please help I can not understand this. I need an ...

MATH PLEASE CHECK IT!!2 - m-2/m-5*m+5/m-2=-1 If your problem is this: (m - 2)/(m...

math - use the numbers 1,2,3,4,5,6,7,8 and 9 one time make a true math equation...

Algerbra - how do you solve 7(3x+4)=8(2x+5)+13 expand the parenthesis...I will ...

physics - Consider a 626N weight held by two cables. The left hand cable had ...